2008
DOI: 10.1557/proc-1067-b03-02
|View full text |Cite
|
Sign up to set email alerts
|

1T Memory Cell Based on PVDF-TrFE Field Effect Transistor

Abstract: Interest in PVDF-TrFE copolymers as ferroelectric material for Memory application is driven by the prospect of having low cost, low operating voltage and fully organic device. Some previous studies reported FET designs using copolymers [refs 1,2] but none of these structures were fully integrated on silicon wafers and using a MOSFET fabrication process. We present for the first time the integration of a PVDF-TrFE (70%-30%) layer into a standard n-MOS transistor through a quasi-standard semiconductor technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Many experimental studies on the development of the NC-FET with an SS of <60 mV/decade have been reported. [38][39][40][41][42][43][44][45][46][47][48] Unfortunately, their results do not satisfy the requirements of hysteresis-free and low-operation voltage. Nevertheless, the physics of the NC-FET is still a topic of debate, as discussed in many studies.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental studies on the development of the NC-FET with an SS of <60 mV/decade have been reported. [38][39][40][41][42][43][44][45][46][47][48] Unfortunately, their results do not satisfy the requirements of hysteresis-free and low-operation voltage. Nevertheless, the physics of the NC-FET is still a topic of debate, as discussed in many studies.…”
Section: Introductionmentioning
confidence: 99%